2005
DOI: 10.1002/anie.200501478
|View full text |Cite
|
Sign up to set email alerts
|

Highly Regio‐ and Enantioselective Asymmetric Hydroformylation of Olefins Mediated by 2,5‐Disubstituted Phospholane Ligands

Abstract: Asymmetric hydroformylation (AHF) is a powerful synthetic methodology that allows conversion of olefins into optically active aldehydes in a single step [Eq. (1)].[1] The aldehyde group is one of the most versatile functional groups and can be readily transformed into a variety of high-value-added chiral chemicals, such as amines, imines, alcohols, and acids.[2]Even though AHF offers great promise to the fine-chemical industry, this reaction has not been utilized on a commercial scale because of several remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
2
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(78 citation statements)
references
References 22 publications
2
69
2
5
Order By: Relevance
“…The chiral ligands chosen for initial studies on the hydroformylation of dimethylacrylamide were (R,R)-PhBPE, [13] (R,R)-Chiraphite, [7,10] (R,R)-Kelliphite, [7,8] the phosphine-phosphite ligands denoted POP, [14] while later studies used the (S,S,S) or (R,R,S)-Diazaphos-SPE ligand, developed by Landis and co-workers [12] (see Figure 1). The ligand to Rh ratio was 1.25:1, since in many many experiments with a wide variety of alkenes, we have observed that ratios of 1.1-1.5 generally give the best results.…”
Section: Resultsmentioning
confidence: 99%
“…The chiral ligands chosen for initial studies on the hydroformylation of dimethylacrylamide were (R,R)-PhBPE, [13] (R,R)-Chiraphite, [7,10] (R,R)-Kelliphite, [7,8] the phosphine-phosphite ligands denoted POP, [14] while later studies used the (S,S,S) or (R,R,S)-Diazaphos-SPE ligand, developed by Landis and co-workers [12] (see Figure 1). The ligand to Rh ratio was 1.25:1, since in many many experiments with a wide variety of alkenes, we have observed that ratios of 1.1-1.5 generally give the best results.…”
Section: Resultsmentioning
confidence: 99%
“…[1,2] This attention for these P-heterocycles can be ascribed to the incessant search for novel structures, suitable as chiral ligands in asymmetric catalysis, pursued by researchers involved in the field of ligand development. In this regard, chiral phosphacycle-based ligands, which as a consequence of their ring constraints bear unique steric and electronic properties often remarkably different from their acyclic counterparts, are a new intriguing class of enantio-inductors for asymmetric transformations.…”
Section: Introductionmentioning
confidence: 99%
“…[4a,4b] An increasing variety of chiral phosphacycles of different ring extensions, ranging from four to seven units, have since then been prepared and applied successfully in asymmetric catalysis. [2,3,5,6] Benzo-fused phenoxaphosphanes, a class of conjugated phosphorus-based heterocycles, were initially introduced by Mann and Millar in the late 1950's and since then have found applications mostly in the development of new polymeric materials. [7,8] The potential of these cyclic analogues of triphenylphosphane in catalysis has remained hitherto tion of enantiopure phosphanes 3a,b was assigned unequivocally by means of X-ray crystal structure determination for complex 9a and by combination of NOE( unexpressed as is demonstrated by the very few articles regarding the applications of these compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other remarkable C 2 -symmetric ligands, derived from mannitol, successfully applied in asymmetric hydrogenation are the 2,5-disubstitued phospholane ligands (Duphos derivatives) 7 and 8 [14] and the related DIOP, [15] analogue. These 2,5-disubstitued phospholane ligands have recently been identified as excellent ligands for the rhodium-catalysed asymmetric hydroformylation providing high turnover rates and enantioselectivities for styrene, allyl cyanide, vinyl acetate [16] and [2.2.1]-bicyclic olefins. [17] We have recently reported the synthesis of C 2 -symmetric diphosphinite ligands 9 and 10 derived from carbohydrates with a furanoid backbone.…”
Section: Introductionmentioning
confidence: 99%